2016
DOI: 10.1186/s13059-016-1038-5
|View full text |Cite
|
Sign up to set email alerts
|

An alternative novel tool for DNA editing without target sequence limitation: the structure-guided nuclease

Abstract: Engineered endonucleases are a powerful tool for editing DNA. However, sequence preferences may limit their application. We engineer a structure-guided endonuclease (SGN) composed of flap endonuclease-1 (FEN-1), which recognizes the 3′ flap structure, and the cleavage domain of Fok I (Fn1), which cleaves DNA strands. The SGN recognizes the target DNA on the basis of the 3′ flap structure formed between the target and the guide DNA (gDNA) and cut the target through its Fn1 dimerization. Our results show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…The CRISPR/Cas9 system allows targeted genome editing, including frameshift knockout, gene insertion, and alteration, under the guidance of a specific guide RNA (gRNA) 1. Since the first system engineered from Streptococcus pyogenes Cas9 endonuclease,2 many Cas9 variants (e.g., Staphylococcus aureus Cas93), analogues (e.g., CRISPR/Cpf14 and FEN‐1/FokI fused endonuclease5) have emerged. To date, delivery of these gene editing systems relies mainly on viral vectors or electroporation 6.…”
Section: Introductionmentioning
confidence: 99%
“…The CRISPR/Cas9 system allows targeted genome editing, including frameshift knockout, gene insertion, and alteration, under the guidance of a specific guide RNA (gRNA) 1. Since the first system engineered from Streptococcus pyogenes Cas9 endonuclease,2 many Cas9 variants (e.g., Staphylococcus aureus Cas93), analogues (e.g., CRISPR/Cpf14 and FEN‐1/FokI fused endonuclease5) have emerged. To date, delivery of these gene editing systems relies mainly on viral vectors or electroporation 6.…”
Section: Introductionmentioning
confidence: 99%
“…() and Xu et al . () reported DNA‐guided and structure‐guided genome editing tools, respectively. We attempted both the methods; however, unfortunately, none of the methods showed detectable activity in B. mori (data not published).…”
Section: Current Prospective and Future Directionsmentioning
confidence: 99%
“…Although the two-component CRISPR/Cas9 system seems considerably simple for most trained molecular biologists, researchers continue to develop more genome editing tools. Gao et al (2016) and Xu et al (2016) reported DNAguided and structure-guided genome editing tools, respectively. We attempted both the methods; however, unfortunately, none of the methods showed detectable activity in B. mori (data not published).…”
Section: Simplicity and Efficiencymentioning
confidence: 99%
“…In addition to the CRISPR‐Cas system, Xu et al . engineered a novel structure‐guided endonuclease (SGN) to implement targeted DNA cleavage in vivo and in vitro .…”
Section: Perspectivesmentioning
confidence: 99%